ESTIMASI ZONA POTENSIAL PENANGKAPAN IKAN (ZPPI) PROVINSI BENGKULU MENGGUNAKAN CITRA SATELIT MODIS AQUA - Rina Julita; Mr. Mujiono (JFMR (Journal of Fisheries and Marine Research), 2019)
The research aims to; (1) knowing the traditional parameters of the Bengkulu province community in determining fishing zones, (2) mapping the potential fishing zones (ZPPI) in the West Coast waters of Bengkulu province. The method used is interviewing and processing chlorophyll-a images and sea surface temperature extracted through MODIS Aqua images on average monthly for 12 months. The results of the study stated that traditional parameters in determining ZPPI by both Bengkulu and North Bengkulu fishermen were based on; a) hills / mountains, temperature, currents, and brightness of sea water, lead fishing, coral / mud, towers and trees. The most potential fishing zones are in the waters of the Southwest, namely North Bengkulu and Muko-muko districts, and on the southeast side are in South Bengkulu regency. While in the middle, such as Bengkulu and Seluma cities have almost no fishing zones with high potential for fishing.